Adipokinesand Ghrelin Rolein Regulation of Ovarian Function in Obesity - A. I. Abdusalamova; O. A. Bettikher; K. A. Rudenko; O. A. Belyaeva; A. E. Neimark; I. E. Zazerskaya (Ожирение и метаболизм, 2023)
There is a great worldwide trend in the incidence of obesity, which is increasing with each passing year among all populations, including women of reproductive age. Given the impressive list of diseases associated with obesity, as well as the negative inverse correlation of the severity of obesity with fertility, this problem is global not only in the social sphere, but it also becomes demographically significant.Along with other pathogenetic mechanisms leading to persistent anovulation, an imbalance in adipokine production by adipose tissue can also serve as one of the important links in the development of reproductive dysfunction. Despite apparent interest in this topic, a large number of previously discovered adipokines are still not studied. Among adipokines, the effects of adiponectin and leptin on reproductive function are best known. Alterations in adiponectin and leptin levels can affect hypothalamic-pituitary-gonadal signaling, folliculogenesis, oogenesis and steroidogenesis. In addition, leptin is involved in the initiation of puberty, regulation of the menstrual cycle, and changes the balance between proliferation and apoptosis in ovarian cells. The leading causes of reduced fertility, infertility, and IVF failure in obese patients are mechanisms that promote the formation of chronic anovulation, delay the maturation of oocytes, reduce their quality, and/or lead to changes in endometrial susceptibility. These effects can be caused by an imbalance in the concentrations of leptin and adiponectin (leptin excess and adiponectin deficiency), lead to endometrial dysfunction, disruption of implantation and early embryogenesis. These changes, in turn, can affect just as the likelihood of spontaneous conception, so the effectiveness of assisted reproductive technologies and subsequent gestation.Thus, the study of potential pathogenetic pathways of fertility regulation in obesity, one of which is the subject of this review, is an important area for further study.